HOW ACCURATELY CAN NRM/SIRM DETERMINE THE ANCIENT PLANETARY MAGNETIC FIELD INTENSITY? - Yu Y. (My University, 2006)
The present study tested grain-size dependence of thermoremanent magnetization (TRM)/saturation isothermal remanent magnetization (SIRM) as well as its stability against demagnetization. The TRM/SIRM ratio is dependent on the grain-size of magnetite, suggesting that a strong constraint on grain-size characterization is necessary to be used as a paleointensity proxy in planetary magnetism. In addition, the TRM/SIRM ratio increases as the alternating-field increases for fine-grained magnetite. Accuracy of TRM/SIRM was investigated using historic Showa lava erupted in 1946. It was observed that the natural remanent magnetization (NRM)/SIRM ratio of 0.032 is comparable to the field intensity of 46.80 μT. However, the uncertainty of NRM/SIRM was an order of magnitude larger than that of the companion Thellier estimation. Therefore, the NRM/SIRM ratio can only provide crude estimations on the absolute planetary magnetic field intensity. In practice, anisotropy correction is advisable to reduce the scatter of NRM/SIRM. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANISOTROPY CORRECTION; MAGNETITE; METEORITE; NRM/SIRM; PALEOINTENSITY